2018
DOI: 10.1186/s12903-018-0653-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in patients with recurrent aphthous stomatitis

Abstract: BackgroundLower serum vitamin D levels, a major public health problem worldwide, has been found to be associated with various infectious diseases, cancers, autoimmune and dermatological diseases. The serum levels of vitamin D in patients with recurrent aphthous stomatitis are not clear. We investigated the vitamin D levels in patients with recurrent aphthous stomatitis.MethodsForty patients with recurrent aphthous stomatitis (Group I) and 70 healthy controls (Group II) included in the study. The characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 27 publications
(26 reference statements)
0
30
0
4
Order By: Relevance
“…Khabbazi et al 16 reported that vitamin D levels were significantly lower in study group than control group. Similarly, Oztekin and Oztekin 2 found decreased levels in the serum of patients with recurrent aphthous stomatitis compared to healthy control patients. Also, Bahramian et al 17 reported that the serum levels of vitamin D in patients with recurrent aphthous stomatitis were significantly less than that in healthy individuals.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Khabbazi et al 16 reported that vitamin D levels were significantly lower in study group than control group. Similarly, Oztekin and Oztekin 2 found decreased levels in the serum of patients with recurrent aphthous stomatitis compared to healthy control patients. Also, Bahramian et al 17 reported that the serum levels of vitamin D in patients with recurrent aphthous stomatitis were significantly less than that in healthy individuals.…”
Section: Discussionmentioning
confidence: 81%
“…We also found no correlation between vitamin D status and the severity of the disease. To the best of our knowledge, there are only a few studies conducted in adult population on the relationship between recurrent aphthous stomatitis and vitamin D. 2,5,16 But the results are controversial. Krawiecka et al 5 conducted a study in Poland and found no significant difference between patients with recurrent aphthous stomatitis and healthy individuals in terms of vitamin D levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this preliminary study, we aimed to better understand periodontopathic patient evaluation, especially from a perspective of inflammatory markers and vitamin D assessment, through an ELISA assay. The evaluation of vitamin D levels is commonly performed in serum, and only a few studies have assessed its levels in gingival crevicular fluid (GCF), which is considered as serum exudate [30,31]. Both blood and GCF sampling have relative invasiveness linked to their withdrawal method.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions usually heal spontaneously within 7-10 days without scarring [2][3][4]. Most affected patients usually develop more than one ulcer in each episode, and experience several episodes annually [2] Despite the high prevalence, and the extensive research on RAS, its etiology is still unclear; instead, a number of predisposing factors have been proposed including, but not limited to, genetic predilection, hematologic factors, immunologic defects, vitamins deficiencies, emotional stress, and local trauma [2,3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%